1998
DOI: 10.1073/pnas.95.13.7368
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hypoxia-inducible factor 1 activity by nitric oxide donors in hypoxia

Abstract: Nitric oxide (NO) is known to have various biologic and pathophysiologic effects on organisms. The molecular mechanisms by which NO exerts harmful effects are unknown, although various O 2 radicals and ions that result from reactivity of NO are presumed to be involved. Here we report that adaptive cellular response controlled by the transcription factor hypoxia-inducible factor 1 (HIF-1) in hypoxia is suppressed by NO. Induction of erythropoietin and glycolytic aldolase A mRNAs in hypoxically cultured Hep3B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(133 citation statements)
references
References 52 publications
5
127
0
1
Order By: Relevance
“…2, lanes 5, 7, and 9). These results with SNP are consistent with those of Sogawa et al (32), who tested a hypoxia-inducible reporter gene with SNP and two other NO donors.…”
Section: Effect Of Carbon Monoxide and Nitric Oxide On The Induction supporting
confidence: 82%
See 1 more Smart Citation
“…2, lanes 5, 7, and 9). These results with SNP are consistent with those of Sogawa et al (32), who tested a hypoxia-inducible reporter gene with SNP and two other NO donors.…”
Section: Effect Of Carbon Monoxide and Nitric Oxide On The Induction supporting
confidence: 82%
“…The hypoxic induction of erythropoietin (27), vascular endothelial growth factor (28,29), and other genes (30) was markedly blunted in the presence of carbon monoxide (CO), a molecule whose only established biological function is binding to ferrous atoms on heme groups. Subquently, another heme ligand, nitric oxide (NO), was shown to exert a similar effect (29,31,32). In addition to hypoxia, HIF-1 can be activated by the transition metal Co 2ϩ as well as by iron chelation (33).…”
mentioning
confidence: 99%
“…We cannot exclude, however, that a chemical reaction of NO or one of its metabolites with PHD causes enzyme inactivation at a moiety other than Fe 2ϩ . A number of reports from independent groups suggested that treatment of cells with NO donors under hypoxic conditions inhibited HIF-1␣ accumulation and transactivation of HIF-1 (Liu et al, 1998;Sogawa et al, 1998;Huang et al, 1999). At present we do not have an explanation for the difference between normoxic and hypoxic NO effects.…”
Section: Discussionmentioning
confidence: 56%
“…Regulation of HIF-1 activity by NO is likely to be of (patho)-physiological relevance but molecular mechanisms have not been defined yet. Initial observations suggested that NO inhibits hypoxia-induced HIF-1␣ stabilization and HIF-1 transcriptional activation (Liu et al, 1998;Sogawa et al, 1998;Huang et al, 1999). More recent studies indicated that chemically diverse NO donors or enhanced endogenous NO formation by inducible NO-synthase or NO formation in a coculture system under normoxic conditions provoked HIF-1␣ stabilization, HIF-1 DNA-binding, and activation of downstream target gene expression (Kimura et al, 2001;Sandau et al, 2001aSandau et al, , 2001bZhou et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…20 The results showed that SIN-1 at 500 mM inhibited cell proliferation to a much greater extent than did CoCl 2 at 50 mM, while SIN-1 treatment alone or in combination with 50 mM CoCl 2 did not induce cell death (Figure 7b …”
Section: -Morpholinosydnonimine Inhibited Hif-1a Accumulation and Hrmentioning
confidence: 94%